Promoting Intergenerational Approach in Local Governance for Inclusive, Sustainable, and Resilient Pandemic Recovery: The Case of the City of Malolos - Valenzuela, Victoria P.; Cruz, Micahella S. Dela; Allanodin, Aliah A.; Morales, Rose Anne D.; Valenciano, Rhoda L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
The study aimed to find ways to promote an intergenerational approach for inclusive, sustainable, and resilient pandemic recovery of the City of Malolos by assessing the current efforts of the city and the willingness to participate of four hundred selected citizens. The findings revealed that the City of Malolos has continuously worked to prevent and mitigate the virus while considering partnerships with non-governmental and private organizations, interagency collaborations, and community inputs. The study also revealed that respondents across different generations are willing to participate and collaborate with people from different age groups towards pandemic recovery: to voice out the needs and interests of people of their age and people younger than them; to understand and be understood; to feel a sense of fulfillment and community. The researchers suggested that the city should further encourage organization and cross-sectoral collaborations, promote understanding between generations, mobilize social media platforms, conduct educational forums, and apply intergenerational lenses to recognize challenges and opportunities concerning the pandemic.